2008
DOI: 10.1007/s00484-007-0142-3
|View full text |Cite
|
Sign up to set email alerts
|

A biometeorology study of climate and heat-related morbidity in Phoenix from 2001 to 2006

Abstract: Heat waves kill more people in the United States than hurricanes, tornadoes, earthquakes, and floods combined. Recently, international attention focused on the linkages and impacts of human health vulnerability to urban climate when Western Europe experienced over 30,000 excess deaths during the heat waves of the summer of 2003-surpassing the 1995 heat wave in Chicago, Illinois, that killed 739. While Europe dealt with heat waves, in the United States, Phoenix, Arizona, established a new all-time high minimum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(64 citation statements)
references
References 17 publications
3
51
0
6
Order By: Relevance
“…Detrimental impacts can be further expanded to athletic performance, work and behaviour [2]. Many studies have specifically noted that urban dwellers show overall decreased health and functionality in everyday life [3], and also higher heat related mortality [4,5]. Through the use of accurate TC models applied to bioclimatic urban design, improvement of outdoor spaces more conducive to recreational activities can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Detrimental impacts can be further expanded to athletic performance, work and behaviour [2]. Many studies have specifically noted that urban dwellers show overall decreased health and functionality in everyday life [3], and also higher heat related mortality [4,5]. Through the use of accurate TC models applied to bioclimatic urban design, improvement of outdoor spaces more conducive to recreational activities can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…3. Statistically, as presented by Golden et al (2008) these indicate that either 24-h maximum temperature or 24-h average heat index has the strongest correlation to calls for service during this time frame.…”
Section: Correlation Analysis and Extended Validationmentioning
confidence: 82%
“…One study in Phoenix, AZ found a lag of only three hours in heat-related morbidity (Golden et al, 2015), thus current day ambulance calls (a measure of morbidity) were used in this study.…”
Section: Study Areamentioning
confidence: 99%